Educational Challenges of University Students in the Pandemic:: Analysis of the Perception of Students of the Accounting Sciences Course at Polo Petrolina-PE/Juazeiro-BA - de Lima Galvão, Wesley Fernando (2023)
This article aims to analyze the perception of students in accounting science courses about the educational challenges for higher education imposed by the coronavirus (covid-19) pandemic. To this end, the tools were initially analyzed as well as the adaptation of the online/remote teaching system used unexpectedly due to the need caused by the aforementioned pandemic at the beginning of 2020. The focus of the research revolves around obtaining information about the process of adapting students to the new tools used by teachers and the new teaching methodologies adopted for the performance of activities in remote mode. The methodology used was exploratory-descriptive, of a quali-quanti nature, having as a procedure the bibliographic research and case study. The sample is composed of 106 students from the accounting sciences courses in Petrolina-PE and Juazeiro-BA. The results indicate that, despite the difficulties imposed by the current scenario, a reasonable number of respondents demonstrate that they are managing to overcome barriers and are partially satisfied with the novelties used in the academic environment, however, with some reservations, such as the question of motivation for development of scientific research activities, something that can be improved in order to strengthen this new teaching model.